Sun Yefang, Social Needs versus Economic Efficiency in China, Editado, traducido y con introducción de K. K. Fung, New York, M. E. Sharpe, Inc., 1982, XXX + 149 pp. - Romer Cornejo Bustamante (El Colegio de México, A.C., 1983)
-